The effect of infection on mortality in acute coronary syndrome patients at Dr. Sardjito General Hospital, Yogyakarta - Putri, Naila Vinidya; Anggrahini, Dyah Wulan; Bagaswoto, Hendry Purnasidha (Indonesian Journal of Biomedicine and Clinical Sciences, 2024)
Ischemic heart disease is the second most significant health burden in Indonesia and the world. The prevalence of coronary heart disease patients in Yogyakarta is predicted to experience a continuous increase. In Sardjito Hospital, mortality rate of acute coronary syndrome (ACS) patients reaches 15%, with pneumonia infection identified as one of the predictors. Despite this high mortality rate, there is a lack of studies addressing the contribution of infectious comorbidities to mortality incidence among ACS patients. This study aimed to investigate the e ffect of infectious comorbidities on the incidence of mortality among ACS patients and its mortality rate in Sardjito Hospital. This study used a cross-sectional design in 794 patients diagnosed with ACS and registered in the SCIENCE registry from January to December 2022 at Sardjito Hospital. The analysis was conducted using the Chi-square method to determine the effect of infectious comorbidities on mortality among ACS patients and a logistic regression test to evaluate the correlation between variables. Based on bivariate analysis, it was found that infectious comorbidities increased mortality rate among ACS patients (p<0.001, OR=2.22[1.46-3.38]), reaching 5.2%. The bivariate analysis between confounding factors and outcome of patients showed that obesity, dyslipidemia, and revascularization significantly influenced the results of ACS patients. Based on multivariate analysis, it was discovered that infectious comorbidities, obesity, diabetes, dyslipidemia, and revascularization had a significant association with mortality of patients with ACS. Furthermore, infectious comorbidities increased the odds of mortality for ACS patients by 2.04 times. Infectious comorbidities increased the incidence of mortality in ACS patients by 2.04 times with mortality rate of 5.2%.